Can Remifentanil Use in Obstetrics be Improved by Optimal Patient-controlled Analgesia Bolus Timing?. Issue 4 (December 2015) - Rehberg, B.; Wickboldt, N.; Juillet, C.; Savoldelli, G.
Abstract : ( Br J Anaesth. 2015;114(2):281–289)